2019
DOI: 10.1111/jdv.15601
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapy for onychomycosis in patients with diabetes at risk for foot ulcers: a randomized, quadruple‐blind, sham‐controlled trial (LASER‐1)

Abstract: Background Patients with diabetes mellitus are at high risk for onychomycosis, which is related to the development of foot ulcers. Objective The aim of this study was to evaluate the safety and efficacy of the treatment of onychomycosis with local laser therapy. Methods In a single‐centre, randomized (1:1), quadruple‐blind, sham‐controlled trial, patients and microbiological confirmation with diabetes mellitus, at risk for developing diabetic foot ulcers (Sims classification score 1, 2) and a clinical suspicio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
13
0
7
Order By: Relevance
“…Some of the hypotheses already published are the heat fungicidal action over fungi, keratin proteins denaturation, the possible laser influence on cellular oxidative reactions, and changes in host immune modulation. [11][12][13][14] The results of this and other studies 9,10 suggest that laser therapy is not effective in treating onychomycosis. Until now laser treatments have not kept their promises in onychomycosis treatment, and well-designed successful clinical trials are still missing.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Some of the hypotheses already published are the heat fungicidal action over fungi, keratin proteins denaturation, the possible laser influence on cellular oxidative reactions, and changes in host immune modulation. [11][12][13][14] The results of this and other studies 9,10 suggest that laser therapy is not effective in treating onychomycosis. Until now laser treatments have not kept their promises in onychomycosis treatment, and well-designed successful clinical trials are still missing.…”
Section: Discussionmentioning
confidence: 67%
“…The fewer positive fungal cultures could be easily explained as an effect of the mechanical abrasion effectively decreasing fungal load from the nail, leaving less material for positive fungal culture. 8 Also other treatment studies of laser did not show effects on fungal cure: A randomized, quadruple-blind, sham-controlled trial from Nijenhuis-Rosien et al 9 with 63 patients showed no significant differences in a complete and microbiological cure rate of onychomycosis between four treatment sessions (baseline and after 2, 4, and 12 weeks) with Nd-YAG laser (wavelength 1,064 nm, fluency 20 J/cm 2 , spot size 3 mm, pulse rate of 5 Hz, power 10 W, and pulse duration 132 ms) and sham procedure in patients with diabetes. Before starting with (laser or sham) treatment, all affected nails were ground.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 302 PubMed initial search results, 182 clinical trials (28,352 participants) met inclusion criteria and were included in the final analysis 6–186 . The PRISMA study selection process is detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, trials were relatively short, with an average follow-up of 32.5 weeks (SD: 14.3; range: 13.04–62.0 weeks). RCTs on photodynamic and laser monotherapies had a similar average follow-up of 35.3 weeks (SD: 11.5; range: 24.0–52.0 weeks) [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], which suggests that procedural studies, in general, lack the long-term follow-up that is sufficient to determine efficacy of onychomycosis treatment. Furthermore, in our review, some monotherapy and combination arms did not demonstrate efficacy for severe onychomycosis cases [ 35 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%